Epilation for minor trachomatous trichiasis: four-year results of a randomised controlled trial. - Esmael Habtamu; Saul N Rajak; Zerihun Tadesse; Tariku Wondie; Mulat Zerihun; Birhan Guadie; Teshome Gebre; Amir Bedri Kello; Kelly Callahan; David C W Mabey; Peng T Khaw; Clare E Gilbert; et al. (Public Library of Science (PLoS), 2015)
BACKGROUND:Trachomatous trichiasis (TT) needs to be managed to reduce the risk of vision loss. The long-term impact of epilation (a common traditional practice of repeated plucking of lashes touching the eye) in preventing visual impairment and corneal opacity from TT is unknown. We conducted a randomized controlled trial of epilation versus surgery for the management of minor TT (fewer than six lashes touching the eye) in Ethiopia. Here we report the four-year outcome and the effect on vision and corneal opacity. METHODOLOGY/ PRINCIPAL FINDINGS:1300 individuals with minor TT were recruited and randomly assigned to quality trichiasis surgery or repeated epilation using high quality epilation forceps by a trained person with good near vision. Participants were examined six-monthly for two-years, and then at four-years after randomisation. At two-years all epilation arm participants were offered free surgery. At four-years 1151 (88.5%) were re-examined: 572 (88%) and 579 (89%) from epilation and surgery arms, respectively. At that time, 21.1% of the surgery arm participants had recurrent TT; 189/572 (33%) of the epilation arm had received surgery, while 383 (67%) declined surgery and had continued epilating ("epilation-only"). Among the epilation-only group, 207 (54.1%) fully controlled their TT, 166 (43.3%) had minor TT and 10 (2.6%) had major TT (>5 lashes). There were no differences between participants in the epilation-only, epilation-to-surgery and surgery arm participants in changes in visual acuity and corneal opacity between baseline and four-years. CONCLUSIONS/ SIGNIFICANCE:Most minor TT participants randomised to the epilation arm continued epilating and controlled their TT. Change in vision and corneal opacity was comparable between surgery and epilation-only participants. This suggests that good quality epilation with regular follow-up is a reasonable second-line alternative to surgery for minor TT for individuals who either decline surgery or do not have immediate access to surgical treatment.